1954
DOI: 10.1085/jgp.37.6.775
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Formaldehyde on the Oxygen Equilibrium of Hemoglobin

Abstract: It is now generally agreed that the S shape of the curve for the oxygenation of mammalian hemoglobin (fraction oxygenated ~s. oxygen pressure) virtually implies interaction between the four heroes attached to each hemoglobin molecule. In other words, a hemoglobin molecule will react more readily with oxygen after some of its heroes have been oxygenated (1-3). The intramolecular mechanism of this interaction is still very obscure.The problem is often attacked by consideration of the effects of changes in pH (1)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

1956
1956
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 6 publications
(9 reference statements)
0
6
0
Order By: Relevance
“…2 disulfide links formed). The pH dependence of the effect of mersalyl on heine-heine interaction parallels the increasing sensitivity of --SH groups to oxidation found by Mirsky and Anson. Formaldehyde also increases the oxygen affinity and reduces heine-heine interaction (Guthe, 1954). Thus mercuric chloride, mersalyl, --SH oxidation, and formaldehyde all have very similar effects.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…2 disulfide links formed). The pH dependence of the effect of mersalyl on heine-heine interaction parallels the increasing sensitivity of --SH groups to oxidation found by Mirsky and Anson. Formaldehyde also increases the oxygen affinity and reduces heine-heine interaction (Guthe, 1954). Thus mercuric chloride, mersalyl, --SH oxidation, and formaldehyde all have very similar effects.…”
Section: Discussionmentioning
confidence: 93%
“…Actually, it is not shifted significantly. On the other hand, Guthe (1954) has shown that formaldehyde shifts the log ps0 vs. pH curve towards lower pH a very considerable amount. It therefore seems likely that formaldehyde, in contrast to mersalyl, binds an oxygen-linked acid group in addition to its binding of--SH groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Experiments in the 1950s did, however, show a separate relationship between formaldehyde and haemoglobin. For example, in 1954, Karl F Guthe14 demonstrated that formaldehyde greatly increases the oxygen affinity of haemoglobin (more than tenfold when pH is near 7) 14. Further evidence is needed to corroborate our proposal that formaldehyde exposure may cause methaemoglobinaemia.…”
Section: Discussionmentioning
confidence: 69%
“…The methemoglobinemia was treated by a 1 mg/kg dose of intravenous methylene blue and the patient fully recovered within 3 days. While the aetiology in this case remains undetermined due to co-exposure with various volatile components in the products, the methemoglobinemia was most plausibly explained by the occupational formaldehyde exposure ( de Vere, Moores, Dhadwal, & Karra, 2020 ) [A], as some early experiments in the 1950s demonstrated that formaldehyde may greatly increase the oxygen affinity of haemoglobin ( Guthe, 1954 ) [E]. The case may also offer a mechanistic explanation for previous cases of fatal poisonings in connection with formaldehyde-containing hair-straightening products ( Monakhova et al, 2013 ) [E].…”
Section: Aldehydes [Sed-15 1439 1513; Seda-31 409; Seda-32 437; Seda-33 479; Seda-34 377; Seda-36 339; Seda-37 273; Seda-38 211mentioning
confidence: 99%